2018
DOI: 10.1021/acs.joc.8b01555
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed N-Formylation of Amines through Tandem Amination/Hydrolysis/Decarboxylation Reaction of Ethyl Bromodifluoroacetate

Abstract: Ethyl bromodifluoroacetate (BrCFCOOEt) was first used as the N-formylating reagent in the copper-catalyzed N-formylation of amines. A range of primary, secondary, cyclic arylamines, and aliphatic amines underwent the N-formylation smoothly to furnish the N-formamides in moderate-to-excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Concerning the reaction pathway, it is not clear yet. However, based on the above experimental results and literatures, [ 24‐31 ] difluoromethylene carbene was involved as the key intermediate.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Concerning the reaction pathway, it is not clear yet. However, based on the above experimental results and literatures, [ 24‐31 ] difluoromethylene carbene was involved as the key intermediate.…”
Section: Resultsmentioning
confidence: 73%
“…There is no substitution position on the right side, so it can only happen in the 5th position. E undergoes a dehydrofluorination reaction in a strongly alkaline medium to form ketoester F , [ 30 ] intermediate F is hydrolyzed again to obtain keto acid G , and finally, G is decarbonated again to form final product 4a . To date, this reaction has realized the conversion of aldehyde groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we tried the aza-bidentate ligand-independent protocol to make arylamines N -formylation. Zhang’s work showed N ∧ N-bidentate ligands and organophosphorus ligands were effective for the N -formylation . We investigated the effect of our synthetic compounds as ligands in this reaction.…”
mentioning
confidence: 83%
“…Formamides are an important class of organic compounds which possess a very wide range of applications in synthetic chemistry such as Vilsmeier formylation reactions 1,2 and as polar solvents in various organic reactions and medicinal chemistry. 3 By statistical gures, it is found that nearly onefourth of all pharmaceuticals drugs such as paracetamol, formoterol, captopril and chloramphenicol have amide bonds (Fig.…”
Section: Introductionmentioning
confidence: 99%